The Effect of Coffee Grounds Extracts on The Nutrient Utilization and Growth Performance of Tilapia (Oreochromis niloticus) - Ramdani, Nursuci; Diamahesa, Wastu Ayu; Mukhlis, Alis (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The study examines the effects of supplementing coffee grounds to commercial feed on the growth, feed utilization and survival rates of Nile tilapia (Oreochromis niloticus). Given that feed quality and environmental conditions significantly impact fish productivity, the inclusion of coffee grounds, rich in antioxidants and potential immunostimulants, was hypothesized to enhance fish growth and health. The experiment, conducted over 45 days, involved five treatments with varying coffee ground concentrations (0%, 2%, 4%, 6%, and 8%) within a Completely Randomized Design (CRD). Each treatment was replicated three times, resulting in a total of 15 experimental units. Results indicated significant improvements in growth parameters, including absolute weight and length, relative growth, and specific growth rates, particularly at the 6% concentration. However, feed conversion ratio (FCR) and feed utilization efficiency (EPP) did not show significant differences. The study concludes that a 6% coffee ground concentration is optimal for promoting tilapia growth without adversely affecting feed efficiency.